(untitled) (The Journal of Economic Concerns, 2024)
Cooperatives and microfinances are regarded as a vehicle of development. The history of cooperatives and microfinance development is relatively short which dates back to the 1970s. With the assistance of cooperatives and microfinances, households can expand opportunities for income generation. Small size of loan, group savings, small-scale entrepreneurs, diversified utilization and simple and flexible terms and conditions on credit are the determining characteristics of microfinance and cooperatives. Basically this study is based on the review of past studies and research documents and has tried to collect detail information regarding the history, success and failure of microfinance and cooperatives. It covers the information of advanced countries as well as developing countries like Nepal. In course of research, the study found that cooperatives and microfinance have contributed too many households including backward people, women and marginalized groups. It has assisted to poverty eradication, inequality reduction, women empowerment, unemployment reduction which all result to economic development. These outcomes lead to the success of cooperatives and microfinance whereas public policy issues, fraud of the management team, lack of accountability, unproductive use of cooperatives and microfinance lead towards its failure. On the basis of the findings, it can be concluded that there is rapidly expanding number and size of cooperatives and microfinance institutions in many parts of the world, and in course of time these are moving towards commercial sector rather than being oriented to backward people.